Core level spectroscopies locate hydrogen in the proton transfer pathway – identifying quasi-symmetrical hydrogen bonds in the solid state. Issue 9 (19th February 2020) - Stevens, Joanna S.; Coultas, Sarah; Jaye, Cherno; Fischer, Daniel A.; Schroeder, Sven L. M.
Abstract : Snapshots of hydrogen locations between non-ionic and ionic states with XPS reveal hydrogen centred in the middle of the continuum in the solid state. Abstract : Short, strong hydrogen bonds (SSHBs) have been a source of interest and considerable speculation over recent years, culminating with those where hydrogen resides around the midpoint between the donor and acceptor atoms, leading to quasi-covalent nature. We demonstrate that X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy provide deep insight into the electronic structure of the short OHN hydrogen bond of 3, 5-pyridinedicarboxylic acid, revealing for the first time distinctive spectroscopic identifiers for these quasi-symmetrical hydrogen bonds. An intermediate nitrogen (core level) chemical shift occurs for the almost centrally located hydrogen compared to protonated (ionic) and non-ionic analogues, and it reveals the absence of two-site disorder. This type of bonding is also evident through broadening of the nitrogen 1s photoemission and 1s → 1π* peaks in XPS and NEXAFS, respectively, arising from the femtosecond lifetimes of hydrogen in the potential wells slightly offset to either side of the centre. The line-shape of the core level excitations are thus related to the population occupancies, reflecting the temperature-dependent shape of the hydrogen potential energy well. Both XPS and NEXAFS provide a distinctive identifier for these quasi-symmetrical hydrogen bonds, paving the way for detailed studies into their prevalence and potentially unique physical and chemical properties.